Characterization of H460R, a Radioresistant Human Lung Cancer Cell Line, and Involvement of Syntrophin Beta 2 (SNTB2) in Radioresistance - Chang-Nim Im; Byeong Mo Kim; Eun-Yi Moon; Da-Won Hong; Joung Whan Park; Sung Hee Hong (Genomics & Informatics)
A radioresistant cell line was established by fractionated ionizing radiation (IR) and assessed by a clonogenic assay, flow cytometry, and Western blot analysis, as well as zymography and a wound healing assay. Microarray was performed to profile global expression and to search for differentially expressed genes (DEGs) in response to IR. H460R cells demonstrated increased cell scattering and acidic vesicular organelles compared with parental cells. Concomitantly, H460R cells showed characteristics of increased migration and matrix metalloproteinase activity. In addition, H460R cells were resistant to IR, exhibiting reduced expression levels of ionizing responsive proteins (p-p53 and γ-H2AX); apoptosis-related molecules, such as cleaved poly(ADP ribose) polymerase; and endoplasmic reticulum stress-related molecules, such as glucose-regulated protein (GRP78) and C/EBP-homologous protein compared with parental cells, whereas the expression of anti-apoptotic X-linked inhibitor of apoptosis protein was increased. Among DEGs, syntrophin beta 2 (SNTB2) significantly increased in H460R cells in response to IR. Knockdown of SNTB2 by siRNA was more sensitive than the control after IR exposure in H460, H460R, and H1299 cells. Our study suggests that H460R cells have differential properties, including cell morphology, potential for metastasis, and resistance to IR, compared with parental cells. In addition, SNTB2 may play an important role in radioresistance. H460R cells could be helpful in in vitro systems for elucidating the molecular mechanisms of and discovering drugs to overcome radioresistance in lung cancer therapy.